Protein nonadditive expression and solubility contribute to heterosis in Arabidopsis hybrids and allotetraploids - June, Viviana; Xu, Dongqing; Papoulas, Ophelia; Boutz, Daniel; Marcotte, Edward M.; Chen, Z. Jeffrey (Frontiers in Plant Science, 2023)
Hybrid vigor or heterosis has been widely applied in agriculture and extensively studied using genetic and gene expression approaches. However, the biochemical mechanism underlying heterosis remains elusive. One theory suggests that a decrease in protein aggregation may occur in hybrids due to the presence of protein variants between parental alleles, but it has not been experimentally tested. Here, we report comparative analysis of soluble and insoluble proteomes in Arabidopsis intraspecific and interspecific hybrids or allotetraploids formed between A. thaliana and A. arenosa. Both allotetraploids and intraspecific hybrids displayed nonadditive expression (unequal to the sum of the two parents) of the proteins, most of which were involved in biotic and abiotic stress responses. In the allotetraploids, homoeolog-expression bias was not observed among all proteins examined but accounted for 17-20% of the nonadditively expressed proteins, consistent with the transcriptome results. Among expression-biased homoeologs, there were more A. thaliana-biased than A. arenosa-biased homoeologs. Analysis of the insoluble and soluble proteomes revealed more soluble proteins in the hybrids than their parents but not in the allotetraploids. Most proteins in ribosomal biosynthesis and in the thylakoid lumen, membrane, and stroma were in the soluble fractions, indicating a role of protein stability in photosynthetic activities for promoting growth. Thus, nonadditive expression of stress-responsive proteins and increased solubility of photosynthetic proteins may contribute to heterosis in Arabidopsis hybrids and allotetraploids and possibly hybrid crops.